Threshold responses of soil microbial communities and functions to 18O-H2O enrichment - Fangying Qu; Lingrui Qu; Yue Liu; Mike Manefield; Bruce A. Hungate; Ember M. Morrissey; Jian Wang; Yi Yang; Juan Piñeiro; Edith Bai; Chao Wang (Soil Biology and Biochemistry, 2026)

Isolation and characterization of Dehalobacter sp. strain UNSWDHB capable of chloroform and chlorinated ethane respiration - Yie K. Wong; Sophie I. Holland; Haluk Ertan; Mike Manefield; Matthew Lee (Environmental Microbiology, 2016)
Summary Dehalobacter sp. strain UNSWDHB can dechlorinate up to 4 mM trichloromethane at a rate of 0.1 mM per day to dichloromethane and 1,1,2‐trichloroethane (1 mM, 0.1 mM per day) with the unprecedented product profile of 1,2‐dichloroethane and vinyl chloride. 1,1,1‐trichloroethane and 1,1‐dichloroethane were slowly utilized by strain UNSWDHB and were not completely removed, with minimum threshold concentrations of 0.12 mM and 0.07 mM respectively under growth conditions. Enzyme kinetic experiments confirmed strong substrate affinity for trichloromethane and 1,1,2‐trichloroethane ( K m = 30 and 62 µM respectively) and poor substrate affinity for 1,1,1‐trichloroethane and 1,1‐dichloroethane ( K m = 238 and 837 µM respectively). Comparison of enzyme kinetic and growth data with other trichloromethane respiring organisms ( Dehalobacter sp. strain CF and Desulfitobacterium sp. strain PR) suggests an adaptation of strain UNSWDHB to trichloromethane. The trichloromethane RDase (TmrA) expressed by strain UNSWDHB was identified by BN‐PAGE and functionally characterized. Amino acid comparison of homologous RDases from all three organisms revealed only six significant amino acid substitutions/deletions, which are likely to be crucial for substrate specificity. Furthermore, strain UNSWDHB was shown to grow without exogenous supply of cobalamin confirming genomic‐based predictions of a fully functional cobalamin synthetic pathway.

Aliphatic organochlorine degradation in subsurface environments - Joanna Koenig; Matthew Lee; Mike Manefield (Reviews in Environmental Science and Bio/Technology, 2015)

Complete chloroform dechlorination by organochlorine respiration and fermentation - Matthew Lee; Adrian Low; Olivier Zemb; Joanna Koenig; Astrid Michaelsen; Mike Manefield (Environmental Microbiology, 2012)
Summary Chloroform (CF, CHCl 3 ) is a recalcitrant and toxic environmental pollutant. In this communication we report for the first time a microbial community capable of complete CF dechlorination by metabolic processes. Cultures derived from subsurface soil (3.5 m) could sustain complete dechlorination of CF at levels of least 360 µM at a rate of 40 µM per day. Scrutiny of CF dechlorination revealed two metabolic processes at work. First, CF was respired to dichloromethane (DCM, CH 2 Cl 2 ), which was then fermented to acetate, hydrogen and carbon dioxide. Elevated hydrogen partial pressures were found to inhibit the fermentation process. Interspecies hydrogen transfer was observed in the form of methanogenesis and acetogenesis. This suggests that the dechlorination process required syntrophic partners to maintain low hydrogen partial pressures. 13 C‐labelled DCM was employed to help elucidate the chemistry of the process and identify bacterial community members involved. CF respiring cultures, where emulsified vegetable oil was supplied as the electron donor and DCM fermenting cultures, where DCM was supplied as the sole organic carbon source were studied separately. Pyrosequencing of these cultures revealed Dehalobacter lineages as a predominant community member in both. Subsequent growth experiments confirmed that the proliferation of Dehalobacter was linked directly to both the dehalorespiration and dehalofermentation processes.

Development of a treatment solution for reductive dechlorination of hexachloro-1,3-butadiene in vadose zone soil - Lachlan H. Yee; Vibeke Aagaard; Angela Johnstone; Matthew Lee; Staffan J. Kjelleberg; Mike Manefield (Biodegradation, 2010)

An appraisal of methods for linking environmental processes to specific microbial taxa - Maria-Luisa Gutierrez-Zamora; Mike Manefield (Reviews in Environmental Science and Bio/Technology, 2010)

Functional and compositional comparison of two activated sludge communities remediating coking effluent - Mike Manefield; Robert I. Griffiths; Mary Beth Leigh; Ray Fisher; Andrew S. Whiteley (Environmental Microbiology, 2005)
Summary The success of engineered microbiological systems is evident in the global application of activated sludge communities to remediate coking effluent. However, there is a lack of understanding of the microbiology underlying treatment efficiency and stability. In this study, two functionally distinct activated sludge pools, treating the same effluent and operating under the same conditions, were examined to establish a relationship between overall diversity and/or functional diversity with respect to process stability. Molecular profiling, sequencing and RNA‐based stable isotope probing were used to examine the bacterial diversity, general composition and functional composition of the most abundant members of the two communities. The inferior process stability in one of the pools could not be explained by reduced total bacterial diversity or evenness. RNA‐based stable isotope probing revealed that both pools harboured an abundant phenol‐degrading Acidovorax species, and that the pool of inferior stability accommodated an additional closely related phenol‐degrading Acidovorax species at high abundance. These results are discussed in the context of deterministic and stochastic models of microbial community assembly.

N ‐acyl‐ l ‐homoserine lactones (AHLs) affect microbial community composition and function in activated sludge - Anna Valle; Mark J. Bailey; Andrew S. Whiteley; Mike Manefield (Environmental Microbiology, 2004)
Summary The role of intercellular signalling in the regulation of genes and phenotypes in a broad range of bacterial species is now firmly established. In contrast, the impact of intercellular signalling on microbial community parameters, such as species diversity and function, is less well understood. In this study the role of N ‐acyl‐ l ‐homoserine lactones (AHLs) in microbial community dynamics in an industrial wastewater treatment system is addressed. Seven proteobacterial strains producing compounds with AHL‐like activity were isolated from the treatment plant. Three of these belong to genera with no previously identified AHL producing species. Addition of AHLs at 2 µM to sludge samples generated changes in both community function (phenol degradation) and composition as determined by length heterogeneity PCR and denaturing gradient gel electrophoresis. Phenol degradation was more stable as a result of the AHL augmentation. A dominant functional member of the Thauera genus was transiently supplanted by a member of the Comomonas genus in response to AHL addition. This suggests that AHLs can play a role in mediating microbial community parameters and has implications for ecosystem function and industrial wastewater treatment.

Enhanced sensitivity of DNA‐ and rRNA‐based stable isotope probing by fractionation and quantitative analysis of isopycnic centrifugation gradients - Tillmann Lueders; Mike Manefield; Michael W. Friedrich (Environmental Microbiology, 2004)
Summary Stable isotope probing (SIP) of nucleic acids allows the detection and identification of active members of natural microbial populations that are involved in the assimilation of an isotopically labelled compound into nucleic acids. SIP is based on the separation of isotopically labelled DNA or rRNA by isopycnic density gradient centrifugation. We have developed a highly sensitive protocol for the detection of ‘light’ and ‘heavy’ nucleic acids in fractions of centrifugation gradients. It involves the fluorometric quantification of total DNA or rRNA, and the quantification of either 16S rRNA genes or 16S rRNA in gradient fractions by real‐time PCR with domain‐specific primers. Using this approach, we found that fully 13 C‐labelled DNA or rRNA of Methylobacterium extorquens was quantitatively resolved from unlabelled DNA or rRNA of Methanosarcina barkeri by cesium chloride or cesium trifluoroacetate density gradient centrifugation respectively. However, a constant low background of unspecific nucleic acids was detected in all DNA or rRNA gradient fractions, which is important for the interpretation of environmental SIP results. Consequently, quantitative analysis of gradient fractions provides a higher precision and finer resolution for retrieval of isotopically enriched nucleic acids than possible using ethidium bromide or gradient fractionation combined with fingerprinting analyses. This is a prerequisite for the fine‐scale tracing of microbial populations metabolizing 13 C‐labelled compounds in natural ecosystems.